THE RELATIONSHIP PATTERN BETWEEN PERSONALITY TRAITS AND LEARNING RESPONSIBILITY - Akpur, Ugur (SCIENTIA SOCIALIS, 2024)
As the interest in the shift from teacher-centred paradigm to student-centred learning pedagogies has increasingly grown in popularity nowadays, it should come as no surprise that scholars and academicians have given their attention to the concept of self-engagement in the learning process. In an attempt to explore the role of personality in self-engagement, this paper aims to assess the relationship pattern between individuals' personality traits and their learning responsibility. A total of 358 students attending a university were recruited for the study. The Ten-Item Personality Inventory (TIPI) and The Learning Responsibility Scale were administered. The findings revealed that learning responsibility correlates positively with emotional stability, conscientiousness, and agreeableness. However, the associations between extraversion and openness with learning responsibility are negative and not significant. The findings have also demonstrated that although agreeableness does not display a significant predictive power, both emotional stability and conscientiousness have a significant influence on learning responsibility.
Keywords: personality traits; learning responsibility; student-centred learning; individual differences; The Big Five; CONSCIENTIOUSNESS; PREDICTORS; MODEL; Education & Educational Research